2022
DOI: 10.3390/gels8020069
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Gel Dosimetry as a Quality Assurance Tool in Functional Leksell Gamma Knife Radiosurgery

Abstract: Highly precise dose delivery to the target (tumor or cancerous tissue) is a key point when brain diseases are treated applying recent stereotactic techniques: intensity-modulated, image-guided radiotherapy, volumetric modulated arc therapy, Gamma knife radiosurgery. The doses in one single shot may vary between tens and hundreds of Gy and cause significant cell/tissue/organ damages. This indicates the need for implementation of quality assurance (QA) measures which are realized performing treatment dose verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The relative depth dose measurements showed a good agreement between the film and gel. A potential of gel dosimetry in small field applications was also shown in [ 37 ] where the results of the gamma knife facility beam profile measurements in small irradiation fields (diameter of 4, 8 and 16 mm) using an nPAG-based dosimeter and Gafchromic films were presented. It was concluded that relatively accurate beam profile data can be obtained using dose gels for small field dosimetry.…”
Section: Introductionmentioning
confidence: 88%
“…The relative depth dose measurements showed a good agreement between the film and gel. A potential of gel dosimetry in small field applications was also shown in [ 37 ] where the results of the gamma knife facility beam profile measurements in small irradiation fields (diameter of 4, 8 and 16 mm) using an nPAG-based dosimeter and Gafchromic films were presented. It was concluded that relatively accurate beam profile data can be obtained using dose gels for small field dosimetry.…”
Section: Introductionmentioning
confidence: 88%
“…Gel dosimeters provide a visual representation of the dose distribution, allowing physicists and clinicians to evaluate treatment accuracy. [ 117 ]…”
Section: Q Uality a Ssurancementioning
confidence: 99%
“…As most polymer gel dosimeters are used with larger doses than those provided in a single fraction, many studies have focused on stereotactic radiosurgery where larger doses are delivered [ 73 , 83 , 234 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 ]. In most of the studies, the emphasis of the treatment validation experiment is on the spatial accuracy rather than on the absolute dose delivery.…”
Section: Polymer Gel Dosimetersmentioning
confidence: 99%